University of Central Punjab (UCP), Lahore, Pakistan‘s Responsibility for SDG‘s and World Complex Challenges Pertaining to its Innovation for Energy and Climate Change Management - Javaria Qais Joiya; Qais Aslam (Universitas Diponegoro, 2021)
One of the important essentials of modern living is energy without which modern world cannot survive and therefore depends deeply on energy usages and energy abusage. What is important to be seen is that more than 7.8 billion people on this planet are burning fossil fuels for their daily needs. Therefore, the challenge for the 21st century is how to conserve this ‘good’ energy and how to reduce its transformation into ‘bad’ energy and at the same time enjoy a sustainable lifestyle through modern inventions of science and technology. The problems facing University of Central Punjab, Lahore (UCP) is on the one hand how to minimise the usage of energy resources and secondly, how to move away from using fosil feuls and toward usage of eco-friendly energy sources for achieving sustainability and abiding by the Goal 7 of the SDG (Affordable and Clean Energy). Keeping sustainable development and energy conservation issues in mind, UCP has already in collaboration with M/S Premier Energy embarked upon the renewable solar energy solutions and 1/4th of the total energy consumption of UCP is being produced through state-of-the-art grid-tired solar system. UCP also promotes the sagacious use of water. In UCP, processor treat sewage water. In addition, UCP promotes the use of filtered drinking Processor treat sewage water. Promote the use of filtered water instead of bottled water.